Analisis Penerapan Good Corporate Governance (Studi Pada Perusahaan Daerah Air Minum Bandarmasih) - Muhammad Rizki Fayad; Saladin Ghalib; Fitriyadi Fitriyadi (Smart Business Journal, 2021)
This research aims to understand and see the practice of good corporate governance principle in Bandarmasih local water company as one of the companies effort to achcieve they vision and mission and in they attempt to fulfill stakeholders expectancy, also giving an overview of the practice good corporate governance which are transparency, accountability, responsibility, independence, fairness and equality according to the basic guidelines good corporate governance of Komite Nasional Kebijakan Governance (KNKG). This research is using qualitative method, with snowball sampling to determine the informant. Data were gathered by interview, observation and document studies. Furthermore, the analysis technique done by data reduction, data preservation, and conclusion. The result is Bandarmasih local water company has apllying the GCG principle well in running the company. Keywords: Good Corporate Governance, Transparency, Accountabillity, Responsibillity, Independency, Fairness